2020
DOI: 10.3390/antibiotics9060310
|View full text |Cite
|
Sign up to set email alerts
|

A Nationwide Survey of Australian General Practitioners on Antimicrobial Stewardship: Awareness, Uptake, Collaboration with Pharmacists and Improvement Strategies

Abstract: Implementing antimicrobial stewardship (AMS) programs is central to optimise antimicrobial use in primary care. This study aims to assess general practitioners’ (GPs’) awareness of AMS, uptake of AMS strategies, attitudes towards GP–pharmacist collaboration in AMS and future AMS improvement strategies. A paper-based survey of nationally representative GPs across Australia was conducted in 2019. Of 386 respondent GPs, 68.9% were familiar with AMS. Respondents most frequently used the Therapeutic Guidelines (TG)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 33 publications
0
27
0
Order By: Relevance
“…We framed this study comparing two nationwide surveys of GPs and CPs on AMS to explore interprofessional perspectives of implementing AMS in collaboration between GPs and CPs. We undertook two nationwide surveys of GPs and CPs across Australia between January and October in 2019.The detailed methodologies of the survey design and survey tools used are found in the published literature [47,48]. The two-stage stratified random sampling method was employed to select nationally representative samples of 2500 GPs and 2160 CPs using the Australasian Medical Publishing Company (Ampco) database [49] and a pharmacy database.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We framed this study comparing two nationwide surveys of GPs and CPs on AMS to explore interprofessional perspectives of implementing AMS in collaboration between GPs and CPs. We undertook two nationwide surveys of GPs and CPs across Australia between January and October in 2019.The detailed methodologies of the survey design and survey tools used are found in the published literature [47,48]. The two-stage stratified random sampling method was employed to select nationally representative samples of 2500 GPs and 2160 CPs using the Australasian Medical Publishing Company (Ampco) database [49] and a pharmacy database.…”
Section: Methodsmentioning
confidence: 99%
“…Two survey tools were developed involving the representatives from the National Centre for Antimicrobial Stewardship (NCAS) and the Department of General Practice of Monash University. A systematic review of GP-pharmacist collaborative AMS strategies, a scoping review of 10 AMS surveys of CPs, and other AMS surveys of GPs were the sources of the survey items [16,20,47].…”
Section: Methodsmentioning
confidence: 99%
“…Antibiotic stewardship programs generate mixed results, using education, decision algorithms, and communication tools to reduce inappropriate antibiotic prescribing for UTIs in nursing homes [ 22 ]. Studies have shown that uptake of antibiotic stewardship can be inadequate, perhaps because attention to implementation barriers is neglected [ 23 , 24 ]. “Tailored” interventions are planned interventions that follow an investigation of factors that explain current practices and seek to uncover reasons underlying the resistance to new practices [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Proposed activities for AMS have been included in the RACGP’s Standards for General Practice, however, this is only a voluntary accreditation process for GP practices 52 . Pharmacists, in general, are well‐placed to be effective stewards of antimicrobials and are able to play a significant role in collaboration with other healthcare professionals, to optimise the quality use of antimicrobials and help achieve the accreditation standards in primary care 53,54 . Potential roles for pharmacists can occur at the following levels: patient, clinical and system, with suggested activities listed in Table 2 55 …”
Section: Operationmentioning
confidence: 99%